Investigation of Musculoskeletal Symptoms (MSS) and Manual Handling Risk Factors (MHRFS) among Students at School - Ridhwan, Nurul Atiqah; Mohd Nasrull Abdol Rahman (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The study aims to investigate musculoskeletal symptoms (MSS) among primary and secondary school students using the Body Symptoms Survey (BSS), assess manual handling risk factors (MHRFs) with the Manual Handling Assessment Charts (MAC), and recommend improvements for student manual handling practices, focusing on heavy school bags, improper carrying techniques, and ergonomic deficiencies.The study employed a mixed-methods approach with 130 volunteer primary and secondary school students in Parit Raja. focusing on musculoskeletal symptoms. Quantitative data, including mean, mode, median, and standard deviation, were analyzed using descriptive statistics. The Body Symptoms Survey and Manual Handling Risk Assessment were integrated to assess and correlate manual handling risk factors impacting student health. The manual handling risk assessment of 130 students identified varying risk levels from carrying heavy school bags. Most students scored low (0-4), indicating no immediate action required. However, a notable portion scored moderate to high (5-16), highlighting the need for prompt interventions to mitigate risks and ensure student safety, particularly for those nearing higher risk levels. The study underscores the need for immediate interventions to improve how students carry heavy school bags, especially for those experiencing ongoing musculoskeletal pain. Future research should focus on long-term impacts, ergonomic interventions, and student perspectives to enhance school safety and health effectively across diverse student populations.